MANAGEMENT OF LATE BLIGHT DISEASE IN KHARIF POTATO AT KARNATAKA - Bairwa, Aarti (Potato Journal, 2017)
Late blight caused by Phytophthora infestans (Mont.) de Bary is one of the most dreaded diseases of potato worldwide and causes 30-50% loss in kharif potato production. It has become one of the major diseases of kharif potato in Hassan district of Karnataka since 2007-2008. Therefore, a survey was conducted during kharif 2012 and 2013 to know the late blight appearance, its severity and losses caused by the disease. The late blight disease severity ranged from 4 to 40% and 0-100% during 2012 and 2013, respectively and the expected yield loss was about 20-30%. In order to manage the disease, experiments were conducted to identify late blight resistant varieties as well as fungicides schedule. Among the varieties tested, Kufri Girdhari recorded the minimum late blight severity (24.0%) followed by Kufri Shailja (30.0%) and Kufri Himalini (40.4%). However, the highest yield was recorded in Kufri Surya (23.5 t/ha) followed by Kufri Himalini (20.9 t/ha). Among the different fungicide schedules, prophylactic spray (just at the time of canopy closure) with mancozeb @ 0.2% followed by second spray with Sectin (fenamidon + mancozeb) @ 0.3% after 7-10 days of 1st spray and 3rd spray with mancozeb @ 0.2% after of 2nd spray recorded lowest disease severity (34.20%) and maximum yield (25.0 t/ha). So the above said variety and fungicide schedule can be used to manage the late blight disease in kharif potato.